Innovative approaches to sustainable construction: a detailed study of rice husk ash as an eco-friendly substitute in cement production - M. Indumathi; G Nakkeeran; Dipankar Roy; Sonu Kumar Gupta; George Uwadiegwu Alaneme (Discover Applied Sciences)
Abstract An immense amount of rice is cultivated globally, leading to the generation of large amounts of rice husk. Unfortunately, this husk is often disposed of in natural settings and lagoons. The alternative use of this material encourages replacing traditional building materials. Rice husk production in India is 31.40 million tonnes, which fills landfills and causes environmental problems. Concrete with this substance helps solve environmental and economic problems. This material's high silica content makes it pozzolanic. Extensive studies have been carried out in recent decades to evaluate the viability of incorporating it into different building construction methods. The sustainable development of the environment and economy of nations has benefited greatly from such research and innovations. Key findings indicate that this material has a positive impact on the strength and durability of concrete, while also contributing to a reduction in carbon emissions. It implications that this material has the potential to reduce construction expenses and encourage environmentally conscious building methods through the reuse of agricultural waste This study summarises historical research on rice husk-based concrete in infrastructure projects. Its physical and chemical features increase compressive, tensile, workability, durability, flexural strength, and water absorption. VOS viewer was used for bibliometric analysis of country and keyword data. The purpose of increasing the compressive strength when using rice husk ash as a replacement in cement is to enhance the durability and load-bearing capacity of concrete.